1997
DOI: 10.1055/s-2007-979080
|View full text |Cite
|
Sign up to set email alerts
|

Raised Plasma Concentrations of Parathyroid Hormone Related Peptide in Hypercalcemic Multiple Myeloma

Abstract: In order to clarify the pathogenesis of hypercalcemia in multiple myeloma, we measured plasma levels of parathyroid hormone related peptide (PTHrP), tumor necrosis factor alpha (TNF-alpha), tumor necrosis factor beta (TNF-beta), intact PTH and, serum 1,25-dihydroxyvitamin D in fifteen patients of multiple myeloma. We also measured serum levels of inorganic phosphorus (iP) and alkalinephosphatase activity (ALP). No significant differences in iP (3.2 +/- 0.4 vs. 4.0 +/- 2.2 mg/dl), ALP (150 +/- 28 vs. 335 +/- 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…PTH does not have a primary role in MM bone disease. PTH levels of MM patients have been found to be similar to those in healthy controls, however, a few hypercalcemic MM patients were reported to have had high levels of PTH related peptide, which may cause hypercalcemia [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…PTH does not have a primary role in MM bone disease. PTH levels of MM patients have been found to be similar to those in healthy controls, however, a few hypercalcemic MM patients were reported to have had high levels of PTH related peptide, which may cause hypercalcemia [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…There is supportive evidence from clinical studies that the capacity of myeloma cells demonstrated in this study to generate PTHrP is associated with the development of hypercalcaemia in vivo . Elevated circulating levels of PTHrP have been observed in a number of studies on hypercalcaemic myeloma patients7–12, and a temporal relationship has been demonstrated between elevation of the serum PTHrP level and the development of hypercalcaemia10, 11. Recent reports have also indicated that certain human myeloma cell lines produce PTHrP in vitro 18, 19.…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of studies which have sought to identify the effector of osteolysis under these conditions has been complicated by the detection of a number of different cytokines in myeloma cell culture supernatant, such as interleukin (IL)‐1β, IL‐6, tumour necrosis factor (TNF)‐α, and TNF‐β, with the capacity to promote osteolysis in this bioassay4–6. PTHrP has also been incriminated on the basis of an observed association between increased circulating PTHrP levels and the development of hypercalcaemia in some myeloma patients7–12, but the capacity of myeloma cells to produce PTHrP in vivo has not been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported an infrequent association between elevated serum PTHrP levels and myeloma although the frequency of elevated serum PTHrP levels is higher in myeloma patients who are hypercalcaemic than those who are not (Horiuchi et al , 1997; Firkin et al , 1998). A study of myeloma bone marrow samples provided immunohistochemical evidence of PTHrP protein production by myeloma cells and evidence of PTHLH ( PTHrP ) mRNA expression by in situ hybridization techniques.…”
Section: Hypercalcaemia In Haematological Disordersmentioning
confidence: 99%